Morphosemantic Analysis of Compound Word Forms Denoting Surgical Procedures - Norton, L. M.; Pacak, M. G. (Methods of Information in Medicine, 1983)
This paper describes a methodology for automated morphosemantic segmentation and semantic interpretation (paraphrasing rules) of medical compound word forms derived from Greek and Latin and denoting surgical procedures. Possible applications of such a procedure in medicine include the construction of computer-based medical dictionaries, automated processing of medical language, facilitation of international communication through national medical language, and vocabulary training for medical and paramedical personnel.
Keywords: Medical Terminology; Componential Morphosemantic Analysis; Automated Compound Word Segmentation; Paraphrasing